2012
DOI: 10.1159/000343309
|View full text |Cite
|
Sign up to set email alerts
|

Aldosterone is not Involved in the Ventricular Remodeling Process Induced by Tobacco Smoke Exposure

Abstract: Background/Aims: Renin-angiotensin-aldosterone system blockade with a mineralocorticoid-receptor antagonist has not yet been studied in exposure to tobacco smoke (TS) models. Thus, this study investigated the role of spironolactone on cardiac remodeling induced by exposure to tobacco smoke. Methods: Male Wistar rats were divided into 4 groups: a control group (group C, n=11); a group with 2 months of cigarette smoke exposure (group TS-C, n=13); a group that received spironolactone 20 mg/kg of diet/day and no c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Regardless of the complexity of the remodeling process, the term is frequently used as a synonym for ventricular enlargement associated with functional alterations after MI [18-21]. Indeed, in experimental models, some, but not all studies showed attenuation of left ventricular dimensions with aldosterone receptor blockade [22-24]. The same fact was observed in clinical trials [25-27].…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the complexity of the remodeling process, the term is frequently used as a synonym for ventricular enlargement associated with functional alterations after MI [18-21]. Indeed, in experimental models, some, but not all studies showed attenuation of left ventricular dimensions with aldosterone receptor blockade [22-24]. The same fact was observed in clinical trials [25-27].…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2 was analyzed as per Tyagi et al [24,25]. In brief, samples were diluted in extraction buffer with 50 mM Tris pH 7.4, 0.2 M NaCl, 0.1 % Triton X, and 10 mM CaCl 2 .…”
Section: Methodsmentioning
confidence: 99%
“…A two-dimensional parasternal short-axis view of the left ventricle (LV) was obtained at the level of the papillary muscles. M-mode tracings were obtained from short-axis views of the LV at or just below the tip of the mitral-valve leaflets, and at the level of the aortic valve and left atrium [29,30,31,32]. M-mode images of the LV were printed on a black-and-white thermal printer (Sony UP-890MD) at a sweep speed of 100 mm/s.…”
Section: Methodsmentioning
confidence: 99%